The Expanse : Cibola Burn - Book 4 - Corey, James S.A. (New York, NY : Orbit, 2014)
"The gates have opened the way to thousands of habitable planets, and the land rush has begun. Settlers stream out from humanitys home planets in a vast, poorly controlled flood, landing on a new world. Among them: the Rocinante, haunted by the vast, posthuman network of the protomolecule as they investigate what destroyed the great intergalactic society that built the gates and the protomolecule. But Holden and his crew must also contend with the growing tensions between the settlers and the company which owns the official claim to the planet"-- Provided by publisher.
Keywords: Life on other planets -- Fiction; Space warfare -- Fiction; Extraterrestrial beings -- Fiction; Science fiction